IDENTIFIKASI DAN MITIGASI RISIKO PEMBANGUNAN INFRASTRUKTUR JALAN LINGKAR BADUNG SELATAN, BADUNG-BALI - I GUSTI AGUNG AYU ISTRI LESTARI; I GEDE ANGGA DIPUTERA; GDE DIKA GRAHITA SUKAWIBAWA (GANEC SWARA, 2022)
Badung is one of the districts in Bali with a very high number of road users so traffic jams often occur. One of the government's efforts to anticipate this congestion is the existence of a plan to implement the South Badung Ring Road Development Project, Badung Bali. The existence of the project plan will certainly cause various kinds of risks that may occur. The purpose of this study is to find out what risks are likely to occur and to minimize the impact of these risks. This research was conducted using a descriptive method with a qualitative approach. The stages are conducting interviews and observations in order to identify, assess and mitigate risks that are classified as major risks. The results of this study indicate that there are 34 (thirty four) identified risks. Of the 34 (thirty four) risks, 10 (29.41%) are classified as unacceptable risk, 18 (52.94%) are classified as undesirable risk, 6 (17.65%) acceptable risk (acceptable) and 0% or no risk classified as negligible (can be ignored). For risks that are classified as major risks, ownership analysis and mitigation are carried out. The number of risk treatments carried out is 13 mitigations or treatments for unacceptable risks and 22 mitigations or treatments for undesirable risks.